A Study on the Measurement of Flexural Strength of Free-form Concrete Panel (Architecture Image Studies, 2025)
With advancements in digital technology and construction techniques in modern times, buildings of diverse geometries are now being constructed. Many of these structures feature curved surfaces and are of large scale, and they are referred to as free-form architecture. Among the exterior panels of such free-form buildings, those made of concrete are termed Free-form Concrete Panels(FCPs). Since these panels are exposed to external environments, they are subjected to various external forces, and thus must exhibit resistance according to their specific geometries. Accordingly, this study aims to measure the bending behavior of FCPs among the various external forces acting upon them. A testing method for flexural strength test measurement will be proposed, and, if necessary, testing equipment will be developed to conduct the experiments. Through this research, differences in strength arising from variations in curved geometries can be identified, and it will also be possible to determine which shapes are most vulnerable to bending loads.